Dentoalveolar changes in post-twin block appliance orthodontic treatment class II dentoskeletal malocclusion - Y Yoana; Eka Chemiawan; Arlette Suzy Setiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2017)
Background: The analysis of cephalometric radiographs provides information about facial skeletal structures, jaw bone-base relationships, incisive-axial inclination relationships, soft tissue morphology, growth direction and pattern, malocclusion classification and the limitations of orthodontic treatments. In class II malocclusion, the mesiobuccal cusp of the permanent maxillary first molar rests between the first mandibular molar and the second premolar. A twin block appliance is recommended to treat Class II dentoskeletal malocclusion with retrognathic mandible characteristics. Purpose: The aim of this study was to analyze the dentoalveolar alterations in class II dentoskeletal malocclusion with retrognathic mandible characteristics after orthodontic treatment with twin block appliance based on a Steiner analysis. Methods: This research constitutes a retrospective study using secondary data derived from the lateral cephalometric radiographs of patients with Class II malocclusion treated with twin block appliance at the Pediatric Dentistry Department of the Oral and Dental Hospital, Universitas Padjajaran, Bandung. The data was analyzed using a T-test for normally distributed paired data. In cases where data was not normally distributed, a Wilcoxon test was employed. Results: The average measurements showed statistically significant dentoalveolar changes among class II malocclusion patients after twin block appliance treatment when analyzed using the paired t-test based on Steiner method cephalometric radiograph analysis (p < 0.05). Conclusion: It is concluded that a twin block appliance is effective in treating class II dentoskeletal malocclusion with a retrognathic mandible based on dentoalveolar changes resulting from Steiner analysis.